Functional dynamic prosthesis alignment maintained across varying footwear using a modular prosthetic ankle-feet system - Nicole R. Walker; Myrriah P. Laine Dyreson; Juan E. Cave II; Kali R. Mansur; Kelly J. Yun; John M. Looft; Andrew H. Hansen (PLoS ONE, 2025)
Changing footwear often presents a challenge for lower extremity prosthesis users. When prosthesis alignment is completed by the Certified Prosthetist, the prosthetic foot is set at an angle accommodating a single shoe heel rise (shoe heel height minus forefoot height); deviation from this heel rise causes misalignment of the prosthesis. To address this problem, the Rehabilitation & Engineering Center for Optimizing Veteran Engagement & Reintegration (RECOVER) has developed a modular ankle-feet system allowing for the use of footwear of varying heel rises without the need for realignment by the prosthesis user. The primary aim of this study was to understand if clinically acceptable prosthesis alignment is maintained as prosthesis users change between modular foot-shoe sets. Three women transtibial prosthesis users self-selected three pairs of footwear with a heel rise up to 10 cm. Using the modular prosthetic ankle-feet system, participants completed five walking trials per foot-shoe set in the motion analysis laboratory. Reflective markers were used to track the location of the prosthetic socket during walking. These data in combination with center of pressure measurements were used to calculate ankle-foot-shoe rollover shapes and the location of the origin of the best-fit circle for each rollover shape. The locations of the resulting best-fit circle origins indicate prosthesis alignment is maintained within clinically acceptable parameters as users change between foot-shoe sets. These findings have implications for improving footwear options for people with lower-extremity amputations.